HEALTH-BASED PHYSICAL FITNESS LEVEL BY GENDER AMONG FORM SIX SPORTS SCIENCE STUDENTS IN THE STATE OF KEDAH (International Journal of Physiotherapy, 2019)
Background: Physical fitness has a strong relationship with health and academic achievement. This study aims to identify the health-related physical fitness level among Form Six Sports Science students in the State of Kedah by gender.Methods: 225 students (107 male and 118 female) were purposively selected to participate in this descriptive study. This study was conducted using the Prudential FITNESSGRAM® test battery instrument, which introduced by Cooper Institute for Aerobics Research, (1992). Researchers determine the physical fitness level of the subjects using five test items: cardiovascular endurance, muscle endurance, muscle strength, flexibility, and body mass index (BMI).Results: The findings use descriptive statistical analysis to identify the physical fitness level based on health components using the norms developed by Elumalai et al. (2019). The overall fitness analysis showed that almost 50% of boys and girls were in the range of a good level. Around 20% were in the range of moderate and very good respectively. Meanwhile, less than 5% were excellent in both genders. Analysis based on separate components showed most of the subjects, around 80% were in the range of moderate to very good.Conclusion: This study indicates that Form Six Sports Science student's physical fitness should be tested and evaluated before enrolling in Form Six sports Science program. This will ensure that they are healthy and have the quality as expected for future sports personals towards the development of the Malaysian sports industry.